Terminal exon definition occurs cotranscriptionally and promotes termination of RNA polymerase II. - Dye, M; Proudfoot, N (1999)
Analysis of nascent transcription from the human epsilon- and beta-globin genes shows that transcriptional termination occurs within 1.5 kb of the poly(A) site and is dependent on the presence of functional poly(A) signals. Even so, transcripts that have not been cleaved at the poly(A) site are detected up to the termination region, suggesting that there is a kinetic lag between transcription over the poly(A) signal and its effect on transcriptional termination. Surprisingly, mutation of the splice acceptor (SA) of the beta-globin IVS2 also abolishes transcriptional termination. Our results emphasize the interconnection of transcription and RNA processing by showing that the enhancement of 3' end processing by the terminal splice acceptor occurs cotranscriptionally.